Harmonics elimination and reactive power compensation based on novel SDFT-PLL shunt active power filter control approach - Arafa, Osama M.; Mamdouh, Mona M.; Mansour, Ahmed; Elkady, Zeinab (Institute of Advanced Engineering and Science, 2025)
Active power filters are used to reduce current harmonics and compensate for reactive power in non-linear loads. This paper compares two approaches for estimating compensated current for a shunt active filter. The synchronous-reference- frame theory d-q and sliding fast Fourier-Transform algorithms are compared in this study. The comparison is based on the outcomes of simulations. For different load conditions, the results achieved by the approaches mentioned differ greatly. The sliding discrete Fourier transform SDFT approach has revealed the optimum choice. Indeed, sliding discrete Fourier transform-phase-locked-loop or SDFT-PLL is a perfect method also for synchronizing the inverter with a weak noisy grid.